Species of Gyrodactylus von Nordmann, 1832 (Platyhelminthes: Monogenea) from cichlids from Zambezi and Limpopo river basins in Zimbabwe and South Africa: evidence for unexplored species richness - Petra Zahradníčková; Maxwell Barson; Wilmien J. Luus-Powell; Iva Přikrylová (Systematic Parasitology, 2016)

Taxonomy, distribution and prevalence of parasites of tigerfish, Hydrocynus vittatus (Castelnau, 1861) in the Sanyati basin, Lake Kariba, Zimbabwe - Nyasha Mabika; Maxwell Barson; Cobus Van Dyk; Annemariè Avenant-Oldewage (Acta Parasitologica, 2016)
Parasites of the tigerfish

Invertebrate communities in dry-season pools of a large subtropical river: patterns and processes - Tamuka Nhiwatiwa; Tom De Bie; Bart Vervaeke; Maxwell Barson; Maarten Stevens; Maarten P. M. Vanhove; Luc Brendonck (Hydrobiologia, 2009)